Comparison of the effects of symmetric and asymmetric heat load on indoor air quality and local thermal discomfort with diffuse ceiling ventilation. Issue 1 (2nd January 2022) - Zhao, Weixin; Lestinen, Sami; Kilpeläinen, Simo; Kosonen, Risto
Abstract: In this study, indoor air quality and thermal conditions were studied under laboratory conditions with the heat load that was located symmetrically or asymmetrically in the room. Diffuse ceiling ventilation (DCV) was adopted to provide cooling and outdoor air to the room. CO2 concentration, room air temperature and air speed were measured in the test chamber. This study gives insight of both thermal comfort and indoor air quality with different heat load levels and load distribution. The results show that the strength, distribution and the type of heat load have a significant influence on air distribution and thermal comfort. In all cases, the performance of the diffused ceiling ventilation was like fully mixed ventilation. The mean air temperature and speed increase with the heat load, as a result, also draught rate increases, which meant the heat load distribution has effect on local thermal discomfort.